2023
DOI: 10.1038/s41598-023-40036-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus early warning and factor analysis using ensemble Bayesian networks with SMOTE-ENN and Boruta

Abstract: Diabetes mellitus (DM) has become the third chronic non-infectious disease affecting patients after tumor, cardiovascular and cerebrovascular diseases, becoming one of the major public health issues worldwide. Detection of early warning risk factors for DM is key to the prevention of DM, which has been the focus of some previous studies. Therefore, from the perspective of residents' self-management and prevention, this study constructed Bayesian networks (BNs) combining feature screening and multiple resamplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that 18 F-FDG PET is an available non-invasive method to complementally assist the diagnosis and prognosis prediction of epilepsy; it can also help with the intracranial electrode placement and potentially decrease the amounts of invasive EEG tests that need to be conducted (24)(25)(26). However, these studies were also focused on single conventional parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that 18 F-FDG PET is an available non-invasive method to complementally assist the diagnosis and prognosis prediction of epilepsy; it can also help with the intracranial electrode placement and potentially decrease the amounts of invasive EEG tests that need to be conducted (24)(25)(26). However, these studies were also focused on single conventional parameters.…”
Section: Discussionmentioning
confidence: 99%
“…During the model training, the cross-entropy cost function was used to adapt weights during the learning process by minimizing the loss; and the optimal model hyperparameters were tuned by grid search algorithm and evaluated using 10-fold cross-validation. In addition, to fix the group imbalance in our dataset, the best way could be to generate additional samples for minority classes, which means that the model performance to correctly predict the minority class label is getting better by using SMOTE-ENN to balance our data ( 24 ). The SMOTE-ENN combination resampling method strategically integrates the advantages of the SMOTE technique and the Edited Nearest Neighbor (ENN) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes is considered to be one of the three major diseases that seriously endanger human health [151]. It is an illness with a complicated etiology that affects several body organs.…”
Section: Antidiabetic Effectmentioning
confidence: 99%
“…(a) SMOTE-ENN combines the SMOTE and edited nearest neighbor (ENN) techniques and is assigned to the hybrid sampling technique group [183]. SMOTE is an oversampling technique, which generates synthetic samples for the minority class.…”
mentioning
confidence: 99%
“…In order to overcome these disadvantages, the ENN technique is used, which removes samples from both classes [186]. The ENN algorithm can be described as a data cleaning method, which may remove any sample whose class label is different from the class of two or more of its closest neighbors [183]. (b) SMOTE-TL is a hybrid technique, which combines SMOTE and the Tomek links (TL) techniques.…”
mentioning
confidence: 99%